Óxido nítrico inalado para tratamento de infecção por SARS-CoV-2 : um ensaio clínico aberto, paralelo e randomizado - Friedrich, Frederico (2022)
Introduction: In high doses (≥160 ppm), inhaled nitric oxide (iNO) has can act as a broad-spectrum antimicrobial agent. These findings suggest the development of investigations of high-dose iNO treatment of respiratory tract infections, including SARS-CoV-2. Objective: The aim of this study is to test whether inhaling nitric oxide at a concentration of 160ppm at the beginning of the disease reduces the number of days on ventilatory support, hospital length of stay, and improved the clinical score between days 3 and 7 of hospitalization. Methods: We did an open-Label, Parallel, phase 2, Randomized Controlled Trial. Patients hospitalized for COVID-19 aged 10 years or older recruited within the first 48 hours of admission prior to randomization were eligible for enrollment. Participants were randomly assigned (1:1) to receive a single iNO (>160ppm) for 6 hours + standard care (experimental group) or standard care (control group). The primary endpoint was days free of ventilatory support within 15 days from baseline. Primary efficacy analyses were done in the intention-to-treat population, safety was assessed in all patients who received the investigational therapy. This study is registered with rebec.gov.br, RBR-8nfx26. Results: From November 2020 to March 2022, 55 patients were enrolled, 28 allocated to the iNO group and 27 allocated to the control group. One ineligible patient was mistakenly randomized and excluded from analysis. Data from all 54 patients were considered for primary analysis. iNO group had a greater median number of days free of ventilatory support than did patients in the control group (median 11 [IQR, 8-13] vs 8 [IQR, 2.5-10]; between groups difference of 2 days [95% CI 0-4]; p=0.044, and had a lower clinical score at day 3 and day 5; p=0.010 and p=0.033 respectively. The median length of stay was shorter in the nitric oxide group (4.00 days [IQR, 3.00-6.25]) when compared to the control group (7.00 days [IQR,6.00-10.00]); p= 0.004 with a difference of 3 days [95% CI 1-5]. Respiratory failure and mortality did not differ between groups. No adverse events occurred. Conclusions: iNO had a positive effect on the clinical progression of patients hospitalized with moderate COVID-19, reducing the days of supplemental oxygen and the length of stay. The results support the use of iNO 160 ppm to treat hospitalized patients with COVID-19.